Computerized Accounting Systems and Organizational Performance in Local Governments in Uganda A Case Of Rubanda District - Charles, Akandwanaho (Kabale University, 2022)
A Research Dissertation Submitted to the Faculty of Economics and Management Sciences for the Partial Fulfilment of the Requirements for the Award of Master’s Degree in Busines Administration of Kabale University